Ambiguous species boundaries: Hybridization and morphological variation in two closely related Rubus species along altitudinal gradients. Issue 14 (15th June 2020) - Mimura, Makiko; Suga, Mihoko
Abstract: Although hybridization frequently occurs among plant species, hybrid zones of divergent lineages formed at species boundaries are less common and may not be apparent in later generations of hybrids with more parental‐like phenotypes, as a consequence of backcrossing. To determine the effects of dispersal and selection on species boundaries, we compared clines in leaf traits and molecular hybrid index along two hybrid zones on Yakushima Island, Japan, in which a temperate ( Rubus palmatus ) and subtropical ( Rubus grayanus ) species of wild raspberry are found. Leaf sinus depth in the two hybrid zones had narrower clines at 600 m a.s.l. than the molecular hybrid index and common garden tests confirmed that some leaf traits, including leaf sinus depth that is a major trait used in species identification, are genetically divergent between these closely related species. The sharp transition in leaf phenotypic traits compared to molecular markers indicated divergent selection pressure on the hybrid zone structure. We suggest that species boundaries based on neutral molecular data may differ from those based on observed morphological traits. Abstract : We compared clines of leaf morphology and molecular hybrid index at species boundaries of two closely related but ecologically distinct species. The leaf trait clines were steeper than molecular hybrid index clines. Species boundaries might be less obvious than one would conclude from the morphological traits.